Use of pseudotyped viruses to study H3 subtype influenza A viruses circulating in the wild duck reservoir - Cotterill, Sadie (2019)
The Mallard (Anas platyrhynchos) is the world’s most numerous wild duck species and is an important reservoir species for influenza A viruses (IAV). Wildfowl maintain the largest genetic variance of IAV subtypes H1-H16 and N1–N9. The H3 subtype is the most frequently observed low pathogenicity avian influenza (LPAI) and is antigenically and genetically diverse, with the capability to infect mammalian and avian hosts. Previous human IAV pandemics are thought to have originated from avian lineage viruses and are therefore important to monitor. Surface glycoproteins, haemagglutinin (HA) and neuraminidase (NA) are crucial components in interspecies transmission. Current literature on H3 N1–N9 subtypes and the Global Initiative on Sharing All Influenza Data (GISAID) database were examined to determine protein compatibility and to explore the phylogenetic relationship between isolates. Results identified H3N8 as the most frequently observed subtype, H3N2 and H3N6 equally have high prevalence amongst literature and the sequence dataset. All other subtypes were observed at a lower frequency. The phylogeny of the H3 and N1–N9 isolates revealed two clades (Eurasian and North American) which coincided with published studies on IAV lineages. Subsequently, the use of pseudotyped viruses (PVs) to examine the compatibility of the surface proteins and further explore their potential use in serological assays were undertaken. An A/equine/Sussex/1989 (H3N8) PV was generated and tested in conjunction with previously generated PVs of the H3 subtype. The results of MUNANA neuraminidase activity assays concurred with an earlier report, i.e. that the assay was insufficiently sensitive for measuring NA activity in PVs. The pseudotype-based enzyme linked lectin assay (ELLA) was adopted and provided promising results, however demonstrated the need for greater optimisation of PV dilutions to ensure that a suitable curve is generated. The ELLA identified the potential application of a PV generated containing vesicular stomatitis virus envelope glycoprotein (VSV-G) as a replacement for HA, in conjunction with N8 A/equine/Sussex/1989, highlighting the possibility of using VSV-G with any NA combination to measure NA activity and inhibition. Further studies to replicate results are required.